Accountability in the Shadow of Power: A Narrative of Regional Budget Deviations from the Perspective of Public Accountant Ethics - Siti Eliyana; Lilik Purwanti (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2025)
This literature review analyzes the complexity of local budget deviations through a synthesis of the ethical experiences of public accountants within power relations in Indonesia. Using an interpretive qualitative approach and a systematic narrative review method, this study analyzes 40 journal articles from the period 2018-2024 through the lenses of Giddens' structuration theory and institutional theory. The research findings reveal four dominant narratives that shape the phenomenon: (1) professional identity conflicts of accountants facing local political pressures; (2) mechanisms for normalizing deviations through administrative routines; (3) covert resistance strategies employed within power imbalances; and (4) the construction of distorted meanings of performance success within the bureaucracy. This study concludes that budget deviations are not merely individual criminal acts, but rather the result of complex social constructions within dysfunctional power networks. This review contributes to deconstructing the simplistic "perpetrator-victim" dichotomy and develops a contextual "dysfunctional power network" conceptual model for Indonesia. Its practical implications emphasize the need to strengthen institutional protections for public accountants and to reform reward systems based on integrity. Meanwhile, its theoretical implications include the development of a model that integrates structural and agency perspectives. Methodologically, this study contributes through the application of a systematic narrative review in public sector accounting research, with the limitation of focusing on qualitative studies.